Mechanography assessment of fall risk in older adults: the Vietnam Osteoporosis Study. Issue 5 (30th June 2021) - Hoang, Duy K.; Le, Nhan M.; Vo‐Thi, Uyen P.; Nguyen, Huy G.; Ho‐Pham, Lan T.; Nguyen, Tuan V.
Abstract: Background: Jumping mechanography is a technology for quantitatively assessing muscular function and balance in older adults. This study sought to define the association between jumping mechanography parameters and fall risk in Vietnamese individuals. Methods: The study involved 375 women and 244 men aged 50 years and older, who were recruited from the general population in Ho Chi Minh City (Vietnam). The individuals had been followed for 2 years. At baseline, Esslinger Fitness index (EFI), jumping power, force, velocity of lower limbs, and the ability to maintain balance were measured by a Leonardo Mechanograph Ground Reaction Force system (Novotec Medical, Pforxheim, Germany). The incidence of falls during the follow‐up period was ascertained from self‐report. Logistic regression analysis was used to analyse the association between jumping mechanography parameters and fall risk. Results: The average age of participants at baseline was 56.7 years (SD 5.85). During the 2 year follow‐up, 92 falls were reported, making the incidence of fall at ~15% [95% confidence interval (CI), 12.1 to 18.2]. The incidence of fall increased with advancing age, and women had a higher incidence than men (17.6% vs. 10.7%; P  = 0.024). In univariate analysis, maximal velocity [odds ratio (OR) 0.65; 95% CI, 0.52 to 0.82], maximal force (OR 0.83; 95% CI, 0.65 to 1.04), and maximal power (OR 0.68; 95% CI, 0.52 to 0.88) were each significantly associated with fall risk. EFI was not significantly associated with fall risk (OR 1.09; 95% CI, 0.86 to 1.39). However, in a multiple logistic regression model, greater maximum velocity was associated with lower odds of fall (OR 0.38; 95% CI, 0.16 to 0.92). Conclusions: These data suggest that jumping mechanography is a useful tool for assessing fall risk in older adults of Vietnamese background.